Trajectories of Masculinity and Femininity in Tehmina Durrani’s Autobiographical Narrative, My Feudal Lord - Salman, Saad; Syed Hanif Rasool (University of Chitral Journal of Linguistics and Literature, 2023)
Tehmina Durrani, has largely been acclaimed for her audacious depiction of the predicaments of the marginalized segments of Pakistani society. Exploring gender dichotomy affecting the relationship of the narrator and her husband, the paper attempts to trace the trajectory of the split between masculinity and femininity, foregrounding a distressed marital relationship under a clash of interests between spouses. The study accentuates the variance of mental/psychological, emotional, socio-cultural, and religious chasms of the psyches of men and women by grounding the argument in question on the theorizations of masculinity and femininity as contended by Todd.W. Reeser, Linda Mcdowell, R.W. Connell, and feminism as argued by Stephanie Hodgson-Wright, Valerie Sanders, Sue Thornham, and Sophia Phoca. Emphasizing the individual and collective tussles between the narrator and her husband, informed by the gender issues, the study explores that My Feudal Lord unfolds the sheer dissimilarities between the oppressor and the oppressed, swaying between the duality of reason and feeling. Underlining further the marked traits labeled as masculine and feminine, the paper attempts to illuminate the attributes of manhood and womanhood, mainly the notion that the former have had privileges over the latter, resulting in the gender and social polarities between femininity and masculinity.